Profile of Qiang Fu - Tinsley H. Davis (Proceedings of the National Academy of Sciences, 2026)
Atmospheric scientist Qiang Fu uses satellite observations, numerical simulations, and theoretical analysis to investigate how changes across different layers of the atmosphere—and their circulation—are linked to climate change. Early in his career, Fu advanced the understanding and modeling of radiative transfer in Earth’s atmosphere. His recent research centers on stratosphere–troposphere exchanges of air masses and chemical species. In his Inaugural Article Fu, elected to the National Academy of Sciences in 2024, uses satellite observations to track methane loss from the stratosphere and shows that models underestimate the loss of this greenhouse gas.